the effect of material serum concentration on in vitro sperm activation and pregnancy rate in infertile patients - AL- barzanchi, mundhir T.; Al.Noami, Mohammed; Al.anssari, Saeeda; Al-Janabi, fouad (Journal of the Faculty of Medicine Baghdad, 2006)
Background: